2015
DOI: 10.1093/ecco-jcc/jjv169
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Adalimumab in Ulcerative Colitis Refractory to Conventional Therapy in Routine Clinical Practice

Abstract: UC is a progressive disease that may need early aggressive therapy to prevent structural and functional complications. The results of our study demonstrated the favourable efficacy of short- and long-term ADA treatment for patients with UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 12 publications
9
41
0
Order By: Relevance
“…Among those who remained in response (34.1%), 8.3% lost response at week 52. The drug was optimized in 17.8% of the cases (3) . In the Spanish study, dose optimization was observed in 37.5% of the cases, among which 14.3% did not respond even after ADA weekly intake (9) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among those who remained in response (34.1%), 8.3% lost response at week 52. The drug was optimized in 17.8% of the cases (3) . In the Spanish study, dose optimization was observed in 37.5% of the cases, among which 14.3% did not respond even after ADA weekly intake (9) .…”
Section: Discussionmentioning
confidence: 99%
“…Ulcerative colitis (UC) is an inflammatory disease of the large bowel with variable degree of activity, extent and disease course (3) . Up to 15% of patients can present with severe disease at diagnosis (7,30) and in up to 28% it can progress proximally in 10 years (16,30) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Indeed, with increasing recognition of ulcerative colitis as a progressive disease rather than a disorder with periodic flares, 22 the threshold for introducing biologic drugs is steadily being lowered. 23 Few head to head comparisons of different anti-TNFs exist in this situation, although experience suggests that infliximab is preferable for treating active disease. [24][25][26][27][28][29] However, there is less of a consensus on when to introduce biologic agents in patients with Crohn's disease.…”
Section: Starting Anti-tnf Treatmentmentioning
confidence: 99%
“…9 Indeed, perhaps driven by ulcerative colitis being considered more as a progressive disease rather than a disorder with periodic flares, 10 the threshold for introduction of biological therapy is being lowered. 11 NICE has approved the use of biological therapy for moderate ulcerative colitis since 2015 and acute severe ulcerative colitis since 2008. The 2015 NICE guidance (TA329) advocates that the choice of treatment between anti-TNF alpha therapies be made on an individual basis following discussion between the patient and clinician.…”
Section: Biological Drugs In Moderate To Severe Ulcerative Colitismentioning
confidence: 99%